Career Planning in Elite Soccer: The Mediating Role of Self-Efficacy, Career Goals, and Athletic Identity - Monteiro, Ricardo (2021)
This study proposed a model to examine the role of self-efficacy, career goals, and athletic identity (AI) on the career planning of elite soccer players. Two hundred and eighty-one elite soccer players (males) participated in this study. Means, SD, and bivariate correlations were calculated for the variables under analysis. The hypothesized effect of self-efficacy, career goals, and AI on career planning was tested using structural equation modeling (SEM). Results supported the adequacy of the proposed model in explaining the career planning. Career planning is positively influenced by the level of self-efficacy of players through the definition of career goals and is negatively influenced by the level of AI. At the same time, the self-efficacy of players through the definition of career goals positively influenced AI. These findings reinforce the important role of self-efficacy and career goals for the development of AI and career planning and at the same time the opposite relationship between AI and career planning. Thus, it is suggested that a balance on AI, maintaining high levels of self-efficacy and career goals, is required to improve the process of career planning and retirement